Taraxacum litardieri Soest - Štepánek, Jan; Kirschner, Jan (Zenodo, 2013)
Taraxacum litardieri Soest in Acta Bot. Neerl. 6: 416. 1957 (Fig. 1B). Lectotypus (designated by JEANMONOD, 2010): CORSE: “ Punta Artica, éboulis morainique”, 2250 m. env., 2.VIII. 1908, R. de Litardière s.n. (G [G00000879], specimen designated by “*”, n° det. 23231; iso-: L [953133126], cf. JEANMONOD, 2010). Description. – Plants relatively small, (4-)7-14(-18) cm tall, sometimes with several root heads; plant base scarcely covered with dry blackish remnants of old petioles, brownish hairy among petiole bases. Leaves with a relatively simple lobation, usually 5-12 cm long, 1.5-2.5 cm wide, mid-green to [??] paler green, not spotted; leaf blade spatulate to broadly spatulate in outline, ± undivided or usually pinnatilobed or pinnatipartite, rarely pinnatisect, ± obtuse to rounded at the apex, the most common leaf shape with distal 1/2-1/5 undivided and ± entire, proximal part remotely shallowly dentate or lobed, sometimes leaf blade with 2-3(4) pairs of more distinct short, broad, subacute lobes, distal margin usually sigmoid, proximal margin short, ± concave; midrib probably pale; petioles narrow to narrowly winged, usually 1-5 cm long, pale. Scapes usually 3-6, thin, overtopping leaves, glabrous, probably pale green. Capitulum small, 1-1.5 cm in diam., most probably deep yellow to orange-yellow. Involucre ± rounded at base, probably not pruinose. Outer involucralbracts (11-) 13-20, ovatelanceolate, lanceolate to linear-lanceolate, relatively short (as long as 2/5-1/2 of the inner, (3.5-) 4-6 mm long, (1-)2.0-2.5 (-4) mm wide, the outermost one usually ± linear, ca. 1 mm wide, irregularly loosely appressed to erect, blackish, without border or with almost invisible very narrow paler border, not ciliate or very minutely ciliate, flat, with ± paler tip; inner involucral bracts ca. 11 mm long, of ± equal width, sometimes laterally fused, slightly callose below apex. All ligules ± cylindrical, with fused margins, outer ligules striped grey-blackish outside (the whole abaxial side of ligules dark), apical teeth ...